Advertorial: EMA REAFFIRMS POSITIVE BENEFIT-RISK BALANCE OF BAYER’S XARELTO® FOR STROKE PREVENTION IN PATIENTS WITH ATRIAL FIBRILLATION - Advertorial, Bayer (SA Heart Journal, 2017)
Xarelto® for stroke prevention in patients with atrial fibrillation.